Nephrology and public health worldwide - Silva Junior, Geraldo Bezerra da; Ferreiro Fuentes, Alejandro; Nangaku, Masaomi 1964-; Remuzzi, Giuseppe 1949-; Ronco, Claudio 1951- (Basel : Karger, 2021)
Nephrology is one of the fastest growing specialties in medicine. Nevertheless, kidney disease is one of the most serious unmet health needs in many countries. To provide healthcare access with the desirable equity worldwide, the nephrology community needs to discuss this public health issue and take part in decisions for elaboration of public health policies with more justice and equity. This book brings together key current public health problems that affect kidney function and illuminates them in contributions by an international group of nephrologists and general practitioners. The chapters review current knowledge and provide guidelines to manage these conditions and decrease the disease burden. At the end, developments in the digital era and their application to kidney disease treatment are synthesized, and a broader outlook on the future of nephrology is given. Ultimately, the publication aims to gather nephrology and public health expertise from researchers from all over the world, providing a broad vision of issues that must be discussed and overcome to guarantee a better treatment for patients with kidney diseases in the world today.
Keywords: RIÑONES -- ENFERMEDADES; ATENCIÓN MÉDICA; SALUD PÚBLICA